Evaluation and treatment of post-renal transplant cytomegalovirus disease in children - Ali, Mohammed Azar; Sarmath, Madeeha; Shah, Aadam; Mohammed, Fawzan (International Journal of Research in Medical Sciences, 2025)
Cytomegalovirus (CMV) infection typically presents as viremia, a clinical syndrome, or tissue-invasive disease. Identifying risk factors and conducting initial blood investigations, followed by invasive tests when appropriate, are crucial steps to rule out serious tissue-invasive disease. Ganciclovir is the cornerstone of CMV disease treatment, with oral valganciclovir used subsequently based on treatment response. For patients with UL-97 mutant ganciclovir-resistant CMV, foscarnet may be administered, often alongside intravenous immunoglobulin (IVIG), particularly in cases of life-threatening conditions such as CMV pneumonitis. Despite the significance of CMV in this population, there is currently a lack of comprehensive clinical reviews or guidelines specifically addressing the management of post-renal transplant CMV disease in children. This article aims to fill that gap by discussing the various modalities for treating post-renal transplant CMV in children, along with its clinical manifestations and necessary investigations.